Acquisition and elaboration of superficial three-dimensional images in plastic and reconstructive surgery: Applications - C Alfano; Paolo Mezzana; N Scuderi (Indian Journal of Plastic Surgery)
Since 1970, as computed axial tomography machines became easily available and became more sophisticated, image acquisition techniques and analysis improved, developed rapidly and became very useful in medical diagnosis. Today it is possible to examine either the anatomic and functional aspects of deep body organs and tissues including all the minute details as well as their morphological relations with superficial structures. Through precise graphic elaboration programs we can obtain information about spatial relations which was not possible using simply classical clinical examination. It is possible, for example, to "point out" an area of interest from its anatomic context, to carry out virtual cleavage of planes and to measure volumes and distances. New developments in image acquisition systems permit transfer of three-dimensional data directly from existing objects. The three -dimensional computerized axial tomography for deep structures, and the laser scanners for superficial structure, quickly furnish (1-3 seconds for the laser scanners) useful information to plan the surgical operation. When analysing 3D-imaging techniques it is important to appreciate their utility for the planning and the follow up of surgery, particularly for the head and thorax, where the three dimensional evaluation is better than the classic double dimensional system that is incomplete and difficult to interpret. In the future, these systems will be important for the best aesthetic and functional results and above all for reducing the surgical time.